Characterization and Demography of Multidrug Resistance in Patients with Urinary Tract Infections in Lahore, Pakistan - Iqbal, Muhammad Naeem; Ashraf, Asfa; Shahzad, Mirza Imran (PSM Biological Research, 2024)
The aim of the current study was to determine prevalence of multiple drug resistance bacteria among patients suffering from Urinary Tract Infections (UTI’s). This study was carried out at Lahore in Sir Ganga Ram Hospital from 1 March to 30 May 2014. It involved cases with or without clinical symptoms of UTI and they were studied retrospectively. The results revealed a higher prevalence of UTIs among females (71%), in age group 51-75 years (86%), married (73%), house wives (80%), social middle class (85%), illiterate (78%), pregnant women (75%), catheterized (72%) and diabetics (73%). Prevalence of bacteria isolated was Escherichia coli (80%), followed by Staphylococcus aureus (6%), Klebsiella sp. (6%), Pseudomonas sp. (4%) and Proteus sp.(4%). Among the six antibiotics tested, bacterial isolates were more resistant to Ampicillin; with E.coli (100%), S.aureus (85%), Klebsiellasp. (98%), P.aeruginosa (100%), and Proteus mirabilis (100%). Resistance to Ampicillin, Tetracycline, Cefotaxime and Augmentin, commonly prescribed, suggests that increased consumption of a particular antibiotic may contribute to multidrug resistance of uropathogens.